Factoring Polynomials Over Algebraic Number Fields Via Norms - Encarnación, Mark (ISSAC '97 Proceedings of the 1997 international symposium on Symbolic and algebraic computation, 1997)
Proceeding ISSAC '97 Proceedings of the 1997 international symposium on Symbolic and algebraic computation Pages 265-270